Mission-Church Type for College Students: A Qualitative Research on Contextual Ministry in Urban Setting - Jatmiko, Bakhoh; Thawn, Cing Sian; Kawengian, Sherly Ester Elaine (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Yogyakarta, the designated research locus, is recognized as a leading student city, with a substantial academic community consisting of hundreds of universities and hundreds of thousands of students from various geographical locations throughout Indonesia. This condition gives rise to various social dynamics that must be addressed in relation to urgent spiritual issues. The students, who are new adults (18-25 years old) and the subjects of this study, often face a variety of social, emotional, and spiritual challenges associated with this age group's high rate of release in activities and communities of faith. As a result, there is an emerging need to provide related services that prioritize outreach to students, especially in the context of urban settings. This study uses a qualitative study with a phenomenological approach to examine the phenomenon of religious practice in a local church in Yogyakarta that has shown the capacity to develop socialization services for young people. The findings of this study show the importance of understanding the cognitive, social, and emotional development aspects of students as young adults. The personal perceptions and experiences of the study respondents highlighted the needs addressed during their involvement in the faith communities studied. These findings were then formulated into a mission-church-type model for reaching students in urban contexts. The model is based on the following: the adoption of an inclusive community model, the provision of dynamic discipleship, the delivery of relevant teaching, and the implementation of empowerment services.